Characterizing attributes influencing consumers’ behavior when choosing a restaurant using conjoint analysis - Sihlovec, Dominik; Štěrbová, Ludmila, 1957-; Antonovic, Vladan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The goal of this master thesis was to examine and interpret different levels of attributes consumers evaluate when making a choice of visiting a restaurant with particular combination of such criteria. Out of four examined attributes, food quality, average price per meal, restaurant atmosphere and quality of service provided, food quality attribute ranked the most important with 40% importance level, followed by a 25%-important average price per meal, 20% importance in restaurant atmosphere, and lastly, only 15% has been recorded with the quality of service provided. These findings define to what extent and in what particular order these individual attributes are to be taken into account when establishing a restaurant business in terms of the average visitor. Moreover, average levels of attributes have been assessed as statistically insignificant and therefore not being an important driving source behind consumer choice. Difference between male and female sample sizes were also recorded, showing that female sample has deemed the average meal price and the atmosphere attributes more important than its male counterpart. Oppositely, the male sample has expressed a higher importance in terms of food quality and the quality of service provided.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses